2021
DOI: 10.1101/2021.02.20.21252133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the evolution of SARS-CoV-2 under non-pharmaceutical interventions

Abstract: Social and behavioral non-pharmaceutical interventions (NPIs), such as mask-wearing, social distancing, and travel restrictions, as well as diagnostic tests, have been broadly implemented in response to the COVID-19 pandemic. Epidemiological models and data analysis affirm that wide adoption of NPIs helps to control the pandemic. However, SARS-CoV-2 has extensively demonstrated its ability to evolve. Therefore, it is crucial to examine how NPIs may affect the evolution of the virus. Such evolution could have i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In this regard, Banholzer et al ( 2021 ), using a semi‐mechanistic Bayesian hierarchical model, showed that the combination of some nonpharmaceutical interventions leads to a strong reduction in the number of new infections. Furthermore, Gurevich et al ( 2021 ), using evo‐epidemiological model, have shown that the timely application of nonpharmaceutical measures could significantly manage the COVID‐19 crisis and may act to reduce virulence.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…In this regard, Banholzer et al ( 2021 ), using a semi‐mechanistic Bayesian hierarchical model, showed that the combination of some nonpharmaceutical interventions leads to a strong reduction in the number of new infections. Furthermore, Gurevich et al ( 2021 ), using evo‐epidemiological model, have shown that the timely application of nonpharmaceutical measures could significantly manage the COVID‐19 crisis and may act to reduce virulence.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…See Figure 4 Example 6. The SI aps QR model (with asymptomatic, pre-symptomatic, and symptomatic infectious) [37,56] (3.2). See Figure 5; The disease states are i = ( i a , i p , i s , q), and the model is defined by…”
Section: Examples Of Sir-ph Models Used In Covid-19 Modellingmentioning
confidence: 99%
“…This paper contributes to the literature on the theoretical modeling (the impact) of viral mutations and-more specifically-COVID-19 variants (e.g., Roche et al 2011;Basurto et al 2021;Buckee et al 2007;Cao et al 2021;Gabler et al 2021;Gurevich et al 2021;Gordo et al 2009;Griffin et al 2020;Halley et al 2021;Marquioni and Aguiar 2021;Pageaud et al 2021;Rella et al 2021;Rüdiger et al 2020;Williams et al 2021). My contribution is to (a) introduce a parsimonious model of endogenous viral evolution capturing both genetic and antigenic variation (i.e., evolving intrinsic and extrinsic fitness, see Smith et al 2004), as well as imperfect cross-immunity, and (b) use this framework to study aggregate dynamics and the direction of viral evolution under varying containment policies.…”
Section: Introductionmentioning
confidence: 97%
“…It may also, however, be single-peaked, a case in which the species continuously approaches the peak. Gurevich et al (2021) study the evolutionary competition between two distinct strains and find that increased testing favors a test-evasive strain.…”
Section: Introductionmentioning
confidence: 99%